Driving Regional Economic Growth through Tourism Marketing Innovation - Mahjudin Mahjudin; Yeni Ika Pratiwi; Adi Suroso (Journal of Managerial Sciences and Studies, 2025)
The effective marketing of tourism products requires more than mere coordination—it demands strategic and sustained collaboration among stakeholders responsible for tourism development and those directly or indirectly engaged in tourism-related activities. The success of tourism marketing initiatives is strongly influenced by a unified understanding of the strategic role that tourism plays in driving regional economic growth. Prior to the implementation of any marketing strategy, a collective commitment is essential from all relevant parties, acknowledging tourism as a high-yield economic sector and a catalytic driver of regional development and local revenue generation. Recognizing this shared vision enables the formulation of more targeted, inclusive, and sustainable tourism marketing strategies that align with broader economic objectives.